Inclusive crises, exclusive recoveries, and policies to prevent a double whammy for the poor - Mendoza, Ronald U (Archīum Ateneo, 2010)
When it comes to aggregate economic shocks, the poor and the near-poor often face a double whammy. They are often among the most adversely affected by the shock, suffering from crisis effects that push them and their children deeper into poverty. The poor and near-poor are also the least equipped to participate in and benefit from the subsequent recovery. In a grim twist of irony, the very same coping strategies that the poor turn to, in order to survive and weather the crisis are often also among the causes for their inability to recover quickly. This paper reviews the emerging evidence on the impact of the global economic crisis and food and fuel price volatility of 2008-2009, and it analyzes some of the key policy responses deployed by governments. It finds evidence suggesting that once again the poor risk facing a double whammy. To help ensure a more inclusive social and economic recovery, governments could follow a pro-poor countercyclical strategy that preserves social spending and investments as well as uses part of these resources to develop social protection systems. Failure to do so risks translating the effects of the crisis into permanent harm for children, women and poor families.